Differential O-3/O-4 selectivity in the glycosylation of N-dimethylmaleoyl-protected hexosamine acceptors: effect of a conformationally armed (superarmed) glycosyl donor - Della Felice, Franco (2013)
An assessment of the relative O-3/O-4 reactivities of both -methyl glycosides of N-dimethylmaleoyl (DMM) glucosamine and allosamine acceptors protected at O-6 with a benzyl group using a -glucopyranosyl conformationally armed donor (superarmed donor) counterpart is presented. The glycosylation of glucosamine derivatives followed the trends already observed for disarmed donors. On the other hand, the glycosylation of allosamine derivatives gave exclusively substitution on the equatorial O-4, in spite that with a disarmed donor the point of substitution is exclusively on the more hindered, electronically-preferred O-3. The glycosylation of glucosamine derivatives followed the trends already observed for disarmed donors. On the other hand, the glycosylation of allosamine derivatives gave exclusively substitution on the equatorial O-4, in spite that with a disarmed donor the point of substitution is exclusively on the more hindered, electronically-preferred O-3.